Exploration and Identification of the Malacca Plant in North Padang Lawas District, North Sumatra - Elara Resigia; Shalati Febjislami; Nurwanita Ekasari Putri; Sanna Paija Hasibuan (Jurnal Ilmu Pertanian Indonesia, 2026)
The Malacca plant is well-known for its therapeutic benefits and is commonly used to make jam. It is critical to understand the existence and diversity of Malacca plants to preserve germplasm and improve attributes through plant breeding. This study sought to investigate and identify malacca plants in North Padang Lawas Regency. The study was conducted in three subdistricts: Halongonan, Padang Bolak, and Padang Bolak Julu, from May to June 2023. This study employed a survey using purposive sampling. Malacca plant samples from the generative period (flowering and fruiting) were selected. The observation included vegetative characteristics (plant height, stem bark color, leaf size, shape, and color) as well as generative characteristics (flower and fruit shape and color). The findings revealed that there were eight accessions dispersed throughout four settlements. One accession, HT1, is designated as the Phyllanthus emblica species due to changes in leaf, flower, and fruit morphology. In contrast, the remaining seven accessions are categorized as P. indofischeri. The changes can be seen in the shape of the leaf tips, stigma branching, and fruit shape and size. Keywords: indian gooseberry, Phyllanthus emblica, Phyllanthus indofischeri